Growing Pains at Hospitals: Opportunities and Issues of Service Expansion in Maximum Care - Hinkelmann, Juergen; Hasebrook, Joachim Paul; Volkert, Thomas; Hahnenkamp, Klaus (Frontiers in Medicine, 2017)
Purpose: Due to the demographic change morbidity raises the demand for medical hospital services as well as a need for medical specialisation while economic and human resources are diminishing. Unlike other industries hospitals do not have sufficient data and adequate models to relate growing demands and increasing performance to growth in staff capacity and to increase in staff competences. Method: Based on huge medical data sample covering the years from 2010 to 2014 with more than 150,000 operations of the Department for Anesthesiology at the University Hospital Muenster, Germany, comparisons are drawn between the development of medical services and the development of personnel capacity and expertise. Results: The numbers of surgical operations increased by 21% and ‘skin incision to closure’ time by 17%. Simultaneously, personnel capacity grew by 16% largely resting upon recruiting first-time employees. Expertise measured as ’years of professional experience’ dwindled from 10 years to 5.4 years on average and staff turnover accelerated. Conclusion: Static benchmark data collected at fixed reference dates do not sufficiently reflect the nexus between capacity and competence, and do not reflect the dynamic changes in a hospital’s requirements for expertise and specialisation, at all. Staff turnover leads to a loss of experience, which jeopardizes patient safety and hampers medical specialisation. In consequence of the dramatic shortage of medical specialists, drop-off rates must be reduced and retention rates must be increased. To that end, working conditions need to be fundamentally converted for a multi-generation, multi-cultural and increasingly female workforce.